Did the Nazis determine who is a Jew? Jewish identity, Holocaust remembrance and the true story behind Israel's law of return. (2nd January 2023) - Fisher, Netanel
ABSTRACT: The idea that the Nazis dictated (retrospectively) who should be considered a Jew in the State of Israel is widespread. Apparent similarities between Nuremberg and Israel's Law of Return have reinforced the claim that anti-Semitism is the basis for defining Israel's Jewishness. This study's primary goal is to refute this prevailing false understanding by demonstrating how Israel's Jewishness was not based on the reversal of Nazi laws but on positive organic Jewish outlooks. The second goal is to present the original narratives and show how the fallacious Nuremberg myth has evolved. During the 1950s, Israel's founding fathers addressed the 'Who is Jew' question in terms of positive secular Jewish nationalism. The next generation (1970) adopted more religious definitions while being attentive to the evolving inter-marriage reality. In both cases, policy makers saw neither anti-Semitic persecution nor the Holocaust as the basis for defining Jewish affiliation. Only from the 1990s on, due to the need to legitimize the massive immigration of non-Jews, did the 'Nuremberg myth' begin to take root. In addition, the emergence of the Holocaust as a global moral imperative icon and a major source of Jewish and Israeli identification, contributed to the acceptance of the myth.